2007
DOI: 10.2967/jnmt.107.042796
|View full text |Cite
|
Sign up to set email alerts
|

Resting Radionuclide Myocardial Perfusion Imaging in a Chest Pain Center Including an Overnight Delayed Image Acquisition Protocol

Abstract: Emergency department (ED) patients with chest pain (CP) and a nondiagnostic electrocardiogram (ECG) present difficult management decisions. The purpose of this study was to investigate the utility of resting radionuclide SPECT myocardial perfusion imaging (SPECT MPI)-including an overnight delayed image acquisition protocol-in identifying patients presenting to the ED with CP at risk for cardiac events. Methods: Patients presenting to the ED with CP and a nondiagnostic ECG were prospectively enrolled and under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 15 publications
(24 reference statements)
1
6
0
2
Order By: Relevance
“…Our results are within the reported range: from 46% of abnormal MPI (30 of 64 patients) [10], to 16% with abnormal perfusion and 15% equivocal [11], to only 9% (45 of 479 patients) [14]. Our results are within the reported range: from 46% of abnormal MPI (30 of 64 patients) [10], to 16% with abnormal perfusion and 15% equivocal [11], to only 9% (45 of 479 patients) [14].…”
Section: Gated-spect Myocardial Scintigraphysupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are within the reported range: from 46% of abnormal MPI (30 of 64 patients) [10], to 16% with abnormal perfusion and 15% equivocal [11], to only 9% (45 of 479 patients) [14]. Our results are within the reported range: from 46% of abnormal MPI (30 of 64 patients) [10], to 16% with abnormal perfusion and 15% equivocal [11], to only 9% (45 of 479 patients) [14].…”
Section: Gated-spect Myocardial Scintigraphysupporting
confidence: 82%
“…Acute rest myocardial perfusion imaging (MPI) in patients with suspected ACS has a high negative predictive value to exclude MI, as well as future cardiac events during medium-term follow-up (FU) [10][11][12][13][14]. Thus, in general, patients with normal acute rest MPI do not need to be hospitalized, avoiding unnecessary expenses.…”
Section: Introductionmentioning
confidence: 99%
“…20 As many hospitals face situations with decreased inpatient capacity resulting in "bed block," 21 management of chest pain in the ED can possibly decrease in-hospital admissions for evaluation of chest pain. 22 However, the pressures of ED overcrowding 21,[23][24][25][26][27][28] mean that ED resources can become stretched due to the lengthy and costly evaluations of chest pain patients in order to "rule out" ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies even mention that optimal sensitivity of troponin is not reached before 18 hours of symptom onset [13][14][15][16][17][18] . In our study, we found that Troponin I measurements at admission had a sensitivity of 68.8% compared to a 86% sensitivity of scintigraphy during chest pain.…”
Section: Discussionmentioning
confidence: 99%